Pengaruh Penggunaan Media Pembelajaran Interaktif terhadap Minat Belajar Anak Usia 4-5 Tahun di TK Negeri Pembina Kec. Dungingi, Kota Gorontalo - Nurfadilah Muthalib; Nirmala L. Nasief; Asya Anggraini Langindara; Nindi Astuti; Sulastya Ningsih (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This research is motivated by the importance of creating enjoyable learning so that early childhood learning interests can develop better, especially in Pembina State Kindergarten, Dungingi District. The purpose of this study was to determine the effect of the use of interactive learning media on children's learning interests and describe changes in their learning behavior when activities are carried out without media and with interactive media. This study used a quantitative approach with a quasi-experimental method through conventional learning and learning using interactive media in the form of coloring activities. Data were obtained through observations by assessing aspects of enjoyment, focus, activeness, and enthusiasm during the activity. The results showed that children's learning interests in conventional learning only reached an average score of 6 and tended to be low, while in learning using interactive media, it increased significantly to an average score of 13.1. This change was seen from the increase in children's enthusiasm, better ability to focus, and their more active involvement during the learning process. The findings of this study confirm that interactive learning media has an important role in attracting children's attention and creating a more lively and meaningful learning atmosphere, thereby increasing early childhood learning interests